THE RE‐DISCOVERY OF CONTEMPLATION THROUGH SCIENCE: A RESPONSE TO TOM McLEISH: with Tom McLeish, "The Re‐Discovery of Contemplation through Science: Boyle Lecture 2021"; Rowan Williams, "The Re‐Discovery of Contemplation through Science: A Response to Tom McLeish"; Fraser N. Watts, "Discussion of the Boyle Lecture 2021"; and Tom McLeish, "Response to Boyle Lecture 2021 Panel and Participant Discussion.". Issue 3 (28th May 2021) - Williams, Rowan
Abstract: This is a response to Tom McLeish's Boyle Lecture 2021 on the rediscovery of contemplation through science. Several implications are sketched: no single mind can encompass fully what there is to be known; we are likely to be unaware of the full range of what it is that is acting upon us or informing us at any given moment; and the universe that we encounter is a system of interaction and implication in which nothing is simply passive or lifeless.